Policy instruments for limiting global temperature rise to 1.5°C – can humanity rise to the challenge?. (16th March 2018) - Michaelowa, Axel; Allen, Myles; Sha, Fu
ABSTRACT: In order to mobilize the volume of mitigation required to reach a global emissions path consistent with 1.5°C, policy instruments need to be much more stringent than they have been to date. They will have to ensure full decarbonization of key economic sectors within one generation, which will require retirement of high-carbon assets before the end of their technical lifetime. However, political economy shows that only those instruments will be implemented that benefit well-organized interest groups while spreading costs as widely as possible. In the past, this has led to distortions such as emissions trading systems with systemic overallocation of allowances, or carbon taxes that exempt industry. Under favourable lobbying constellations strong subsidy schemes for mitigation can emerge. Renewable feed-in tariffs in Europe persisted for over two decades and were crucial for the breakthrough of wind and solar power technologies. But once competition from China led to the demise of European technology providers and the European population started to feel the pinch from the surcharges on their electricity bills, feed-in tariffs were abolished. Historically, rapid transformations of the nature required to reach 1.5°C built on either lavish public investment into the underlying infrastructure or a general notion of national emergency. Innovative forms of market mechanisms could convince policy makers that mitigation costs are lower than expected and thus accelerate mitigation. For the long-term success of far-reaching mitigation policies, it will be crucial whether they can be framed as harnessing an opportunity or whether they are seen as a grim, but grudgingly accepted response to a societal emergency. Key policy insights Interest groups play a key role in the design of mitigation policy instruments and reduce their efficiency as well as effectiveness. Instruments generating high carbon price levels may in the future be possible if redistribution of revenues is done in a way that soothes the key interest groups. A mixture of market mechanisms for mobilization of mature mitigation technologies with a dedicated public investment programme for emerging technologies seems promising, provided technologies can be 'weaned off' public support at the right point in time. For contentious, 'emergency' technologies such as Negative Emission Technologies (NETs) or Solar Radiation Management (SRM), governance mechanisms on the international level are critical.